PERENCANAAN PEMBANGUNAN DAERAH DALAM ERA TRANSISI KEARAH GLOBALISASI - Fashbir Noor Sidin (JIP ( Jurnal Industri dan Perkotaan ), 2005)
All regions in Indonesia are facing changes transitionally as an effect of the changeof governmental management system from centralistic to de-centralistic followed by switchoverin development paradigm. More ever, economic globalization with all its implications need arelevant local development plan and policy and depend to local reinforcement resources,network development and also the economic of regional integration.